Cover Image. (January 2017) - Nogueira, Andressa Vilas Boas; de Molon, Rafael Scaf; Nokhbehsaim, Marjan; Deschner, James; Cirelli, Joni Augusto
Abstract : The cover image, by Tomokaz Fukuda et al., is based on the Article Expression of Six Proteins Causes Reprogramming of Porcine Fibroblasts Into Induced Pluripotent Stem Cells With Both Active X Chromosomes DOI:10.1111/jcpe.12636 .